Synthesis and evaluation of antifungal properties of a series of the novel 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and its analogues - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Kumari, Ratna; Bhat, Manoj Kumar; Deshpande, Mukund V.; Srinivasan, Kumar V. (Bioorganic & Medicinal Chemistry, 2007)
A series of 2-amino-5-oxo-4-phenyl-5,6,7,8-tetrahydroquinoline-3-carbonitrile and various analogues have been synthesized in excellent isolated yields starting from various arylidenemalononitrile and 3-amino-2-cyclohexen-1-one in 1-propanol as solvent at reflux temperature in the absence of any added catalyst. All the synthesized compounds were evaluated for their antifungal activity. The relationship between functional group variation and biological activity of the evaluated compounds is discussed in the article. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; antiproliferative activity; arylidenemalononitriles; arylquinoline carbonitrile; Michael addition

Novel hybrids of fluconazole and furanones: design, synthesis and antifungal activity - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Chavan, Subhash P.; Chandavarkar, Mohan A.; Iyer, Ramki; Tawte, Amit; Rao, Deepali; Deore, Jaydeep V.; Kudale, Ananada S.; Mahajan, Pankaj S.; Kangire, Gopinath S. (Bioorganic & Medicinal Chemistry Letters, 2011)
During our efforts to develop new antifungal agents, a number of hybrid molecules containing furanones and fluconazole pharmacophores were designed and synthesized. The new chemical entities thus synthesized were tested for their potential as antifungal agents against various fungal strains and it was observed that the compounds with general structure 7 were potent inhibitors of Candida albicans ATCC 24433, Candida glabrata ATCC 90030, Candida tropicalis ATCC 750 and Candida neoformans ATCC 34664 while the fluconazole analogues 12 exhibited antifungal activity against Candida albicans ATCC 24433 and Candida glabrata ATCC 90030. The structure-activity relationship for these compounds is discussed. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures to obtain molecules suitable for development as antifungal drugs. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Fluconazole; Furanones

Stereoselective synthesis and antimicrobial activity of steroidal C-20 tertiary alcohols with thiazole/pyridine side chain - Shingate, Bapurao B.; Liazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2011)
Stereoselective synthesis of novel steroidal C-20 tertiary alcohols with thiazole and pyridine side chain using Grignard reaction of steroidal ketones and thiazole/pyridine magnesium bromide have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: antibacterial activity; Antifungal activity; Grignard reaction; Steroid side chain; Steroidal ketones

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids

Molecular structures and biological evaluation of 2-chloro-3-(n-alkylamino)-1,4-napthoquinone derivatives as potent antifungal agents - Pawar, Omkar; Patekar, Ashwini; Khan, Ayesha A.; Kathawate, Laxmi; Haram, Santosh K.; Markad, Ganesh; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Derivatives of 2-chloro-3-(n-alkylamino)-1,4-naphthoquinone (1-alkyl: methyl; L-1, ethyl; L-2, propyl; L-3 and butyl; L-4) have been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible spectroscopy, LC-MS and single crystal X-ray diffraction studies. Antifungal activity of L-1 to L-4 has been evaluated against Candida tropicalis, Candida albicans and Cladosporium herbarum. The intramolecular hydrogen bonding affects the N-H vibrational frequency in L-2 (3273 cm(-1)). The single crystal X-ray structure reveal that L-1 and L-3 crystallizes in triclinic P-1, whereas L-2 crystallizes in orthorhombic Pca2(1), space group. An extensive intra and intermolecular hydrogen bonding interactions were observed in L-1 to L-3 which leads to molecular association. Intramolecular N-H center dot center dot center dot O hydrogen bonding were observed in L-1 to L-3. Moreover pi-pi stacking interactions were observed between the quinonoid rings of L-1 and L-3, however no such interactions were observed in L-2. An electrochemical study showed molecular association of L-1 to L-4 in DMSO solution. Compounds L-1 to L-4 were found to be potent antifungal agents against all the three strains, especially against C. tropicalis. Amongst these promising antifungal candidates, L-1 showed better activity compared to the clinically administered antifungal drug Amphotericin B and Nitrofurantoin with MIC = 1.25 mu g ml(-1) and MIC = 0.025 mu g ml(-1) respectively against C. albicans. Structure and activity relationship (SAR) study suggest a LogP value of similar to 2.0 and the cyclic voltammetry studies reveals additional chemical processes for L-1, which exhibits maximum activity against all fungal strains. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Antifungal activity; LogP; Naphthosemiquinone; pi-pi stacking

Molecular sieves and ultrasound-assisted synthesis of novel 1,3,4-oxadiazole-2-thiones derivatives as potential antifungal agents - Nikalje, Anna Pratima G.; Nimbalkar, Ms Urja D.; Tupe, Santosh; Vazquez, Julio A. Seijas; Tato, Maria Pilar Vazquez (19TH INTERNATIONAL ELECTRONIC CONFERENCE ON SYNTHETIC ORGANIC CHEMISTRY, 2015)
In the category of microorganism, fungi are considered as the special class of microbes responsible for opportunistic pathogenic infections in humans species. Due to the side effects of commercially available antifungal drugs and the emergence of new drug resistant fungal species in the past few years, has forced the researchers to search for novel and efficient antifungal drug molecules. The 1,3,4-oxadiazoles scaffold is associated with diverse biological activities. The multipurpose use of the Mannich bases in pharmaceutical chemistry promote us to prepare a new series of 5-(4-(benzyloxy)substituted phenyl)-3-((phenyl amino)methyl)-1,3,4oxadiazole-2(3H)-thione as antifungal agents. Herein, we report molecular sieves and ultrasound assisted synthesis of novel series of Mannich bases of the 5-substituted 1,3,4-oxadiazole-2-thiones by amino methylation with paraformaldehyde and substituted primary / secondary amines and their evaluation for antifungal activity. The structures of the newly synthesized compounds were determined by IR, NMR and Mass spectral study. The synthesized compounds exhibited interesting moderate to excellent antifungal activity against Candida albicans (NCIM 3557), Candida albicans(NCIM3471), Candida glabrata(NCIM3237), Cryptococcus neoformans (NCIM 3542), Cryptococcus neoformans(NCIM 3378), Aspergillus fumigates(NCIM 902), Aspergillus niger(NCIM 628) using Flucanazole as a standard reference drug. The synthesised compounds 6d, 6f,6g, 6h and 6j exhibited promising antifungal activity as antifungal agents.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular sieves; Ultrasound -assisted

Ultrasound- and molecular sieves-assisted synthesis, molecular docking and antifungal evaluation of 5-(4-(benzyloxy)-substituted phenyl)-3-((phenylamino)methyl)-1,3,4-oxadiazole-2(3H)-thiones - Nimbalkar, Urja D.; Tupe, Santosh G.; Seijas Vazquez, Julio A.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Nikalje, Anna Pratima G. (Molecules, 2016)
A novel series of 5-(4-(benzyloxy) substituted phenyl)-3-((phenyl amino) methyl)-1,3,4-oxadiazole-2(3H)-thione Mannich bases 6a-o were synthesized in good yield from the key compound 5-(4-(benzyloxy) phenyl)-1,3,4-oxadiazole-2(3H)-thione by aminomethylation with paraformaldehyde and substituted amines using molecular sieves and sonication as green chemistry tools. The antifungal activity of the new products was evaluated against seven human pathogenic fungal strains, namely, Candida albicans ATCC 24433, Candida albicans ATCC 10231, Candida glabrata NCYC 388, Cryptococcus neoformans ATCC 34664, Cryptococcus neoformans PRL 518, Aspergillus fumigatus NCIM 902 and Aspergillus niger ATCC 10578. The synthesized compounds 6d, 6f, 6g, 6h and 6j exhibited promising antifungal activity against the tested fungal pathogens. In molecular docking studies, derivatives 6c, 6f and 6i showed good binding at the active site of C. albicans cytochrome P450 enzyme lanosterol 14 alpha-demethylase. The in vitro antifungal activity results and docking studies indicated that the synthesized compounds have potential antifungal activity and can be further optimized as privileged scaffolds to design and develop potent antifungal drugs.
Keywords: 1; 3; 4-oxadiazoles; Antifungal activity; Mannich reaction; Molecular docking; Molecular sieves; Ultrasound

Synthesis and antimicrobial evaluation of novel 2'-aryl-4-aryl-2,4'-Bisthiazole and 2'-aryl-4-Pyridyl-2,4'-bisthiazole derivatives as potential antibacterial agents - Nalawade, Jitendra; Shinde, Abhijit; Abhale, Yogita K.; Nandurkar, Yogesh; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compound, 2024)
In continuation of our research work to explore bisthiazole derivatives as potential antimicrobial agents, herein we reported the synthesis of a series of novel 2'-aryl-4-aryl-2,4'-bisthiazole (7a-t) and 2'-aryl-4-pyridyl-2,4'-bisthiazole (9a-l) by cyclocondensation of 2-aryl thiazole-4-carbothioamide 5a-d with 2-bromo-1-arylethanone (6a-e) and bromo-1-(pyridin-2/3/4-yl)ethanone (8a-c), respectively. These novel candidates were evaluated in vitro for their antibacterial potential against four pathogenic bacteria, Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), and Bacillus subtilis (NCIM 2162). The synthesized compounds were also screened for their in vitro antifungal activity against Candida albicans (NCIM 3100). Among them, compounds 7b, 9d, 9 g, 9i, and 9 l exhibited excellent antibacterial activity with MIC 2.1 to 12.3 mu g/mL against all tested strains. Most of the compounds reported moderate antifungal activity. The pyridine ring-substituted bisthiazole reported good to excellent antibacterial activity as compared to phenyl ring-substituted bisthiazole. The potential antibacterial activity suggested that bisthiazole derivatives could assist in the development of lead compounds to treat microbial infections.
Keywords: 24'-bisthiazole; antibacterial activity; Antifungal activity; cyclocondensation